2013
DOI: 10.1167/iovs.12-11287
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Bevacizumab-Induced Toxicity for Cultured Human Corneal Fibroblasts

Abstract: Citation: Kim EK, Kang SW, Kim JY, Min K, Kim T. Modulation of bevacizumab-induced toxicity for cultured human corneal fibroblasts. Invest Ophthalmol Vis Sci. 2013;54:3922-3931.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…16 Lactate dehydrogenase (LDH) activity increased at 1.0, 1.5, and 2.0 mg/mL of bevacizumab treatment, but LDH activity after ranibizumab treatment did not increase at concentrations up to 2.0 mg/mL. In the present study, aflibercept had no adverse effects on cell viability at 1.0 and 2.0 mg/mL, at which concentrations bevacizumab and ranibizumab treatment resulted in decreased cell viability.…”
Section: Discussioncontrasting
confidence: 43%
“…16 Lactate dehydrogenase (LDH) activity increased at 1.0, 1.5, and 2.0 mg/mL of bevacizumab treatment, but LDH activity after ranibizumab treatment did not increase at concentrations up to 2.0 mg/mL. In the present study, aflibercept had no adverse effects on cell viability at 1.0 and 2.0 mg/mL, at which concentrations bevacizumab and ranibizumab treatment resulted in decreased cell viability.…”
Section: Discussioncontrasting
confidence: 43%
“…Regarding corneal endothelial cells, while Bevacizumab causes no toxicity, a significant dose dependent reduction of their proliferation is observed [35]. While there are conflicting reports linking Bevacizumab cytotoxicity to corneal fibroblasts [18,36], it was shown that there were neither cytotoxic nor anti-proliferative effects on an immortalized human corneal epithelial cell line [18] while histological assessment showed no significant impact in mouse corneal epithelium [32]. Our data confirm the latter observation in primary human limbal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, only few studies have investigated the toxic effects of anti‐VEGF on retinal cells and very limited information is available on corneal cells (Hosny et al, ; Iriyama, Chen, Tamaki, & Yanagi, ; E.K. Kim et al, ; Thaler et al, ). Our study has addressed the hypothesis that intraocular administration of anti‐VEGF drugs might affect the survival of corneal endothelium by interfering with the NGF pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro VEGF inhibition induces cytotoxic effects on corneal fibroblast and epithelium (E.K. Kim, Kang, Kim, Min, & Kim, 2013;Yoeruek et al, 2007). Moreover, in vivo studies show a detrimental treatment on several corneal features, such as healing and innervation (Dong, Di, Zhang, Zhou, & Shi, 2017; T.I.…”
Section: Introductionmentioning
confidence: 99%